Geo-Congress 2014 Technical Papers 2014
DOI: 10.1061/9780784413272.334
|View full text |Cite
|
Sign up to set email alerts
|

Use of Expanded Shale Amendment to Enhance Drainage Properties of Clays

Abstract: Fine grained soils, in particular clays of high plasticity, are known to have very low values of hydraulic conductivity. Coarse aggregates have been used as a common fill material with fine grained soils for increasing the permeability of clayey soils. Expanded shale has recently been used as an amendment with clay soils to improve its drainage properties. However, limited effort has been made to quantify the effect of expanded shale on the hydraulic conductivity of clayey soils. Therefore, this paper presents… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 5 publications
1
1
0
Order By: Relevance
“…It can be observed that the k eq decreases from 8.7 x 10 -9 to 3.8 x 10 -12 m/s with a corresponding increase in PI from 30 % to 130 %. This trend is consistent with the previous studies (Benson et al 1994;Benson and Trust 1995;Phani Kumar and Sharma 2004;Pal and Ghosh 2013;Mechleb et al 2014). Only a marginal decrement from 3.8 x 10 -12 to 1.9 x 10 -12 m/s was noted for further increase in PI from 130 to 253.…”
Section: Correlation Of K Eq With K 48 Equilibrium Time and Plastici...supporting
confidence: 93%
See 1 more Smart Citation
“…It can be observed that the k eq decreases from 8.7 x 10 -9 to 3.8 x 10 -12 m/s with a corresponding increase in PI from 30 % to 130 %. This trend is consistent with the previous studies (Benson et al 1994;Benson and Trust 1995;Phani Kumar and Sharma 2004;Pal and Ghosh 2013;Mechleb et al 2014). Only a marginal decrement from 3.8 x 10 -12 to 1.9 x 10 -12 m/s was noted for further increase in PI from 130 to 253.…”
Section: Correlation Of K Eq With K 48 Equilibrium Time and Plastici...supporting
confidence: 93%
“…(5) π‘˜ π‘’π‘ž = 0.00024𝑃𝐼 -3.55 Previous researchers have developed several correlations to predict k with the plasticity index (Mechleb et al 2014;Dolinar 2009;Zeng et al 2020). However, most of the correlations are based on natural soils or clay with relatively low plasticity with duration of measurements < 10 days.…”
Section: Correlation Of K Eq With K 48 Equilibrium Time and Plastici...mentioning
confidence: 99%
“…Solutions 𝛿𝛿 of the problem defined by equations ( 9), (10), and (11) have to belong to the Sobolev functional space 𝐻𝐻 1 (πœ”πœ”) of differentiable functions (at least once). This is ensured by the piece-wise polynomial base functions used in standard FEM discretization.…”
Section: Finite Element Implementationmentioning
confidence: 99%
“…Isotropy of the constituents is assumed in this example. Clay permeability is given by π‘˜π‘˜ π‘šπ‘š = 6.5eβˆ’9 m s , expanded shale permeability is given by π‘˜π‘˜ 𝑠𝑠 = 8eβˆ’5 m s and the permeability of interface π‘˜π‘˜ 𝑑𝑑 is variable in this example, ranging from 6.5eβˆ’9 m s to 8eβˆ’3 m s [11]. The size of grains was taken as 𝑑𝑑 = 0.005 m, and the expected grain volume ratio was taken as 20.5%.…”
Section: Example 1 -Hydraulic Conductivitymentioning
confidence: 99%